The subcellular architecture of Paratrypanosoma confusum revealed by CryoET: A window into early trypanosome evolution - Carolina de Lima Alcantara; Matthias Pöge; Wolfgang Baumeister; Juergen M. Plitzko; Wanderley de Souza (Proceedings of the National Academy of Sciences, 2025)
The trypanosomatid Paratrypanosoma confusum represents a key evolutionary link between free-living bodonids and parasitic trypanosomes, yet its cellular architecture remains poorly characterized. Here, we used cryofocused ion beam scanning electron microscopy to prepare lamellae for cryoelectron tomography, enabling nanometer-scale imaging of its ultrastructure in near-native conditions. Our analysis revealed structures never before described in trypanosomatids, including an elaborate cytoskeletal network surrounding the flagellar pocket (FP), desmosome-like connections linking the FP membrane to the flagellum, and a cytopharyngeal-like invagination arising from the pocket. Luminal particles inside the FP were reconstructed in 3D, providing insight into their organization and potential role. The contractile vacuole complex was characterized by two bladders with distinct surface protein coats. Organelles of the biosynthetic and secretory pathways were also resolved, including the Golgi complex, ER exit sites, multivesicular bodies, and a novel multivesicular tubule. We also identified large, autophagosome-like organelles containing intraluminal vesicles and hemifused vesicles, structurally resembling hemifusomes recently described in mammalian cells. These structures, along with periodic striations observed in lipid-rich compartments, suggest conserved mechanisms of vesicle biogenesis. Finally, we describe the nuclear architecture, including well-preserved nuclear pores with defined subcomplexes, chromatin fibers resembling nucleosome arrays, and putative nuclear envelope–chromatin linkages. Together, these findings highlight the cellular complexity of P. confusum , providing insights into the evolution of cellular architecture within trypanosomatids and underscoring the potential of this organism as a model for high-resolution structural studies.